Hubungan Pengetahuan dalam Keteraturan Ibu Hamil Mengkonsumsi Tablet Fe di PMB Winanti, S. TR. KEB - Friskila Friskila; Meldawati Meldawati; Putri Vidiasari Darsono; Susanti Suhartati (Pusat Riset dan Inovasi Nasional, 2025)
Anemia is a condition where a person's body experiences a decrease or the number of red blood cells in the body is below normal limits. this can occur due to a lack of hemoglobin in the body, thereby affecting the amount of red blood cell production. in indonesia, the incidence of anemia in pregnant women is still quite common. one way to prevent anemia in pregnant women is to consume iron (fe) tablets. however, the compliance of pregnant women in consuming iron tablets is still low, which is caused by various factors such as knowledge and regularity which will later influence the formation of health behavior. The aim of this research is to determine the relationship between knowledge and the regularity of pregnant women consuming iron (FE) tablets at PMB Winanti, S.Tr.Keb. This research is research that uses a cross sectional approach. this research uses a non-probability method, namely sampling with 62 respondents. data analysis used in the research includes univariate analysis and bivariate analysis using the chi-square test. The results of the study showed that the majority of respondents had sufficient knowledge, namely 45.2%, and had a balanced regularity, namely regular 50.0% and irregular 50.0%. this was proven by the chi-square statistical test showing the relationship between knowledge and regularity of pregnant women in consuming iron (fe) tablets with a result of 54.8% obtained a p value of 0.023 (p<0.05). From the results of this study, it was concluded that there was a significant relationship between knowledge and the regularity of pregnant women consuming iron tablets.